Congenital malformations of the gastrointestinal tract in neonates at aristide le dantec university hospital in Dakar: Concerning 126 cases - Souleymane Camara; Mbaye Fall; P A Mbaye; S F Wese; F B Lo; Ndour Oumar (Wolters Kluwer Medknow Publications, 2022)
Objective: Congenital malformations of the gastrointestinal tract are one of the major causes of neonatal mortality, especially in developing countries. The aim of this study is to assess the overall management of gastrointestinal malformations. Patients and Methods: The study design is monocentric and retrospective. It includes all newborns aged 1-28 days with malformations of the gastrointestinal tract between 1st January 2014 and 31st December2018, at the Paediatric Surgery Department of Aristide Le Dantec University Hospital in Dakar. Data were collected by studying patient's records and surgical procedures. Results: During the five-year study, 405 newborns with congenital anomalies were admitted to our hospital. A total of 126 newborns were diagnosed with gastrointestinal tract malformations. The incidence was 25.2 cases a year. The sex distribution was 74 boys (58.7%) and 52 girls (41.2%). The mean age at diagnosis was 7.4 ± 3.2 days. Two cases were diagnosed antenatal (1.59%). The mean time to post-natal diagnosis was 6.5 ± 2.1 days. The most common malformation was oesophageal atresia with 43 cases (34.1%). The average time between diagnosis and surgery was 48 h. Out of the 126 cases, 77 (61.1%) received surgery and 49 (38.9%) died before surgery. The main causes of pre-operative death were intricate and dominated by lung infections (42.9%). Among the 77 newborns, who received surgery, 38 (%) had a simple post-operative course, 39 (50.6 %) died. Post-operative deaths were dominated by anaesthetic complications (30.8%), lung infections (46.1%). The overall mortality was 69.8% (n = 88). Conclusion: The low socio-economic status, poor pre-natal diagnosis, prematurity, post-natal diagnostic delay, obsolete medical equipment and the lack of neonatal intensive care units were identified as the major factors for high mortality in neonates with gastrointestinal tract malformations in a developing country.